Stress concentration analysis and fabrication of silicon (100) based ultra-stretchable structures with parylene coating. (November 2020) - Rehman, Mutee Ur; Babatain, Wedyan; Shaikh, Sohail Faizan; Conchouso, David; Qaiser, Nadeem; Hussain, Muhammad Mustafa; Rojas, Jhonathan Prieto
Abstract: Research in stretchable electronics is helping to revolutionize the current electronic industry, particularly in wearable and bio-integrated devices. Cost-effectiveness and easy manufacturing are key factors that contribute to shaping the fate of such technologies. In this work, we present a fabrication method for a novel ultra-stretchable, serpentine-arm spiral (SAS) that was built using a low-cost, standard bulk silicon (100) wafer. However, structural defects that often appear during patterning processes, can lead to stress concentration and structural failure at these sites upon stretching. Parylene coating of the structures is proposed to minimize this stress concentration and improve structure's robustness. Finite element analysis (FEA) was performed to demonstrate the concentration of stress at these defective sites with 2 sizes (0. 1 μ m and 1 μ m ) and at different locations along the arms. Results show that SAS structures reach up to ∼ 80% stress reduction at the defective location compared to straight-arm spirals, while the parylene-coating helps to reduce it up to ∼ 60% further. On the other hand, fabricated uncoated, SAS structures reached up to ∼ 600% prescribed strain before fracture, while parylene-coating improves this maximum admissible strain in ∼ 50%. Additionally, a cyclic tensile test was then performed on the fabricated structures, uncoated and parylene-coated, for over 3000 cycles without fracture. The results observed on coated structures greatly improve the mechanical reliance of such brittle structures, which could be extended to other stretchable configurations. Highlights: Novel and cost-effective fabrication of ultra-stretchable structures is shown. FEA is used to demonstrate stress concentration at defects along the structures. FEA shows that parylene coating helps to reduce stress concentration at defects. Parylene coated structures achieve higher elongation ratios than uncoated ones. Fabricated structures survive cycling tensile test for thousands of cycles. Graphical abstract: